Security of E-health Image in Cloud Environment Using Hybridization of DNA Cryptography: Systematic Literature Review - Dhakal, Madhav; Shakya, Subarna (Nepal Journal of Mathematical Sciences, 2024)
This study focuses on addressing the critical issue of maintaining the confidentiality of valuable and confidential e-health records during transmission through cloud-based environments. It specifically investigates the hybridization of DNA-based computing with other encryption techniques. A systematic literature review was performed using the concept of the PRISMA framework. In this review, 12 kinds of literature related to the security of e-health images are selected from an initial pool of 1117 literatures from databases such as Science Direct, Springer Link, and Google Scholar. The reviewed studies were examined based on key security criteria, including resistance to statistical, differential, and exhaustive attacks, as well as randomness of pixels in images through entropy analysis. The findings indicate that the integration of DNA cryptography with chaotic maps offers a highly effective solution for enhancing data security during transmission. This hybrid encryption approach meets the minimum security requirements across multiple evaluated parameters, providing robust protection for sensitive ehealth image data.